Artificial intelligence coaches on the sidelines: Evaluating readability and quality of soccer training plans from six generative models - Yang, J.; Qin, S.; Ren, D. (International Journal of Sports Science & Coaching, 2025)
Background and Objectives: Generative Artificial Intelligence shows increasing promise for developing personalized training programs in sports science. While previous research has demonstrated its utility in aerobic and resistance training, its effectiveness in generating structured, sport-specific plans for technically demanding, high-contact team sports like soccer remains underexplored. This study aims to assess the readability and quality of soccer training programs generated by six leading generative AI (GAI) models— GPT-4o, GPT-4.5, GPT-o1, GPT-o3-mini, and DeepSeek-R1 and DeepSeek-V3—to assess their feasibility for practical use.